Structure–Property Relationships for Weak Ferromagnetic Perovskites - Moskvin, Alexander (Magnetochemistry, 2021)
Despite several decades of active experimental and theoretical studies of rare-earth orthoferrites, the mechanism of the formation of their specific magnetic, magnetoelastic, optical, and magneto-optical properties remains a subject of discussion. This paper provides an overview of simple theoretical model approaches to quantitatively describing the structure–property relationships—in particular, the interplay between FeO6 octahedral deformations/rotations and the main magnetic and optic characteristics, such as Néel temperature, overt and hidden canting of magnetic sublattices, magnetic and magnetoelastic anisotropy, and optic and photoelastic anisotropy.